Odpowiedzi

2009-09-14T15:03:13+02:00
W(x)/P(x)=A(x) , gdzie A(x)=x²+cx+d
W(x)=P(x)•A(x)
W(x)=(x²+bx+2)•(x²+cx+d)
x⁴-4x³+6x²-ax+2=x⁴+(b+c)x³+(2+bc+d)x²+(bd+2c)x+2d
porównujemy potegi
x⁴: 1=1 ok
x³: -4=b+c ==> c=-4-b
x²: 6=2+bc+d ==> 4=bc+d
x¹: -a=bd+2c
x⁰: 2=2d ==> d=1
rozwiążmy układ równań widząc że d=1
c=-4-b
4=bc+d
z pierwszego podstawiam do drugiego
4=b•(-4-b)+1
b²+4b+3=0
(b+3)(b+1)=0 stąd b₁=-1 b₂=-3
dla b₁=-1 mamy
x³: c=-4+1==> c=-3
x²: 4=-1•-3+1==> 4=4 ok
x¹: -a=-1•1+2•-3==>-a=-7==>a=7

dla b₂=-3 mamy
x³: c=-4+3==> c=-1
x²: 4=-3•-1+1==> 4=4 ok
x¹:-a=-3•1+2•-1==>-a=-3+-2==>a=5
ODP: dla b₁=-1 i a=7 lub b₂=-3 i a=5